2016
DOI: 10.1364/oe.24.016550
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and numerical treatment of modal instability in high-power core and cladding-pumped Raman fiber amplifiers

Abstract: Raman fiber lasers have been proposed as potential candidates for scaling beyond the power limitations imposed on near diffraction-limited rare-earth doped fiber lasers. One limitation is the modal instability (MI) and we explore the physics of this phenomenon in Raman fiber amplifiers (RFAs). By utilizing the conservation of number of photons and conservation of energy in the absence of loss, the 3 × 3 governing system of nonlinear equations describing the pump and the signal modal content are decoupled and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Indeed, commercial fibers have comparatively lower pump absorption due to their smaller mode field, so longer pieces of gain fiber are needed to ensure pump depletion, which might intensify the stimulated Raman scattering (SRS) effect. It has been demonstrated that Raman conversion could cause TMI in Raman fiber lasers [11]. In previous research [12], we found that as the length of the beam delivery fiber after the fiber amplifier increased, the TMI effect was enhanced along with the Raman content in the laser output.…”
Section: Impact Of Stimulated Raman Scattering On the Transverse Mode Instability Threshold 1 Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, commercial fibers have comparatively lower pump absorption due to their smaller mode field, so longer pieces of gain fiber are needed to ensure pump depletion, which might intensify the stimulated Raman scattering (SRS) effect. It has been demonstrated that Raman conversion could cause TMI in Raman fiber lasers [11]. In previous research [12], we found that as the length of the beam delivery fiber after the fiber amplifier increased, the TMI effect was enhanced along with the Raman content in the laser output.…”
Section: Impact Of Stimulated Raman Scattering On the Transverse Mode Instability Threshold 1 Introductionmentioning
confidence: 65%
“…4, shortening the length of the active and passive fibers could be effective to mitigate the SRS effect, but this might limit the application of fibers for lasers requiring delivery at long distances. It should be mentioned that, unlike the laser system presented in the paper, the TMI threshold is independent of the fiber length in Raman fiber lasers [11]. According to previous research [12], the counter-pumped scheme applied to fiber lasers could also suppress SRS and thus increase the TMI threshold.…”
Section: Discussionmentioning
confidence: 83%
“…The energy coupling between different modes on the time scale of millisecond will lead to a sudden degradation in beam quality [10][11][12][13][14]. The TMI threshold will be improved by reducing the core V value [15], increasing the inner cladding diameter [16], employing new fiber structures [17], and controlling the gain dopant distribution in fiber core [18][19][20], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Then the system-based ones referred to shifting pump or signal wavelength [39], [47], changing the linewidth of the signal laser or pump laser [48], [49], controlling the excitation of mode content at injection end of the amplifier [22], adapting the cooling condition [20], [49], and so on. The recent research even disclosed that TMI was related to the occurrence of the nonlinear effects such as the stimulated Brillouin scattering (SBS) [50] and the stimulated Raman scattering (SRS) [51], [52], which provided new cognitions to suppress the TMI in terms of optimizing the system configuration to prevent the nonlinear effects. Furthermore, some latest in-depth research targeting the physical origin of the phase shift between the refractive index grating and the modes interference pattern has proven that the active control of the phase shift by the pump modulation was feasible to mitigate the TMI [30], [53].…”
Section: Introductionmentioning
confidence: 99%